ANTIMICROBIAL USE AND RESISTANCE: SURVEY OF KNOWLEDGE AND AWARENESS OF GENERAL PUBLIC IN CHITTOOR DISTRICT - KAKARLA, PRASANNA LAKSHMI; PEDAPATIKASTURI; SRIVANI, NELLORE; BABU, P. PRAKASH (International Journal of Current Pharmaceutical Research, 2024)
Objective: Antimicrobial resistance (AMR) leads to increased morbidity and mortality. WHO identified AMR as great threat to human health. India with highest bacterial disease burden in the world has rampant antibiotic usage. Natural phenomenon AMR is accelerated by the misuse and overuse of antibiotics. The responsibility of proper usage lies with both the prescribers and general public. Ecological, epidemiological, cultural and socioeconomic factors influence AMR. This study aims to enhance understanding of current public awareness and common behaviors related to antimicrobials, their use and AMR. Methods: Descriptive closed-questionnaire-based face-to-face survey was conducted between January to March 2022 among 400 attendants of patients visiting the tertiary care hospital at Tirupati, Chittoor District. Residents aged>18 y were included; health care providers excluded. Data was collected using WHO questionnaire consisting of two parts. Results: There is widespread antibiotic usage-70% of participants used at least once in past 6 mo. Many respondents were mistaken that head ache (42%) and cold (38%) require antibiotics. Only 66% of respondents knew to take full course of antibiotics. 26% of respondents never heard of antibiotic resistance terminology. 51% of participants had no idea that antibiotic-resistant bacteria can spread among persons. All the respondents agreed that regular hand washing is helpful. Conclusion: Huge knowledge gaps were found along with various misconceptions and misunderstandings in the public. It is imperative to address these gaps as soon as possible to save the potency of available antibiotics. Reasons for misconceptions and ways to dispel them need further studies.